Depth Profiles of Dissolved Oxygen (DO) and Hydrogen Sulfide (H2S) Concentration in a Tropical Freshwater Reservoir - Eka Wardhani; Zulfah Ananda Sugiarti (Universitas Diponegoro, 2022)
This study aims to determine the profile of dissolved oxygen and H2S based on depth in the Jatiluhur Reservoir related to fish culture in floating net cages. The scope of this research is focused on the location of floating net cage cultivation. Dissolved oxygen distribution is classified as a positive heterograde type where dissolved oxygen levels higher in the metalimnion layer due to the photosynthesis process that occurs effectively by aquatic plants and phytoplankton. Jatiluhur Reservoir shows signs of organic pollution, with BOD5 and COD levels exceeding the quality standard. This organic substance comes from the waste of floating net cages. BOD5 and COD values that exceed the quality standard result in increased oxygen consumption during the decomposition process; therefore, a hypoxic layer occurs. This occurrence can cause water conditions to become anoxic, producing H2S gas. The H2S value in the Jatiluhur Reservoir was observed to exceed 0.002 mg/L and showed an increase in the metalimnion layer.